The Effect of Retailer Awareness, Retailer Quality Perception, Retailer Relationship Quality on Customer Loyalty Mediated Customer Satisfaction (A Study of Perahu Salt Brands) - Febry Aditya Pratama; Susilo Toto Raharjo (PT. Publikasiku Academic Solution, 2023)
Salt is a basic need that is no less important than sugar. Almost every household needs consumption salt every day. The existence of salt in everyday life cannot be ignored. The problem that arises in this study is that in recent years sales at perahu salt have experienced fluctuating sales, some complaints about the services provided by Perahu salt principal sales are still unsatisfactory to retailers, especially wholesalers. The purpose of this study is expected to be used by company management as a reference to provide customer satisfaction through the services provided by the principal of the Perahu salt producer through retailer awareness, perceived retailer quality, relationship quality, customer satisfaction and customer loyalty. Quantitative data is taken directly from filling out questionnaires from shops, especially wholesalers in the Central Java area. The results showed that in order to increase customer loyalty in purchasing Perahu salt through retailers, Perahu salt customer satisfaction through retailers needs to be improved. Increasing Perahu salt customer satisfaction through retailers can be done through retailer awareness, perceived retailer quality and relationship quality. Retailers have a big role in driving sales of Perahu salt. When the retailer has the power where the customer realizes the existence of the retailer, the customer will want to make a purchase at the retailer, especially when the customer and the retailer have a good quality relationship such as the customer has a long transaction relationship with the retailer, then this will satisfy the customer more. When customers feel this satisfaction, there is an increase in customer loyalty where customers will want to continue making purchases.